Flexible kinship: caring for AIDS orphans in rural Lesotho. (December 2014) - Block, Ellen
<x xml:space="preserve">Abstract</x> HIV/AIDS has devastated families in rural Lesotho, leaving many children orphaned. Families have adapted to the increase in the number of orphans and HIV‐positive children in ways that provide children with the best possible care. Though local ideas about kinship and care are firmly rooted in patrilineal social organization, in practice, maternal caregivers, often grandmothers, are increasingly caring for orphaned children. Negotiations between affinal kin capitalize on flexible kinship practices in order to legitimate new patterns of care, which have shifted towards a model that often favours matrilocal practices of care in the context of idealized patrilineality.